Determinants of Entrepreneurial Product Innovation - Rezvanny maricar; Rosmiati Rosmiati (Economy Deposit Journal (E-DJ), 2022)
Many studies related to product innovation in entrepreneurship for SMEs (small and medium enterprises) have been carried out in previous studies in various contexts. Requires careful measurement of entrepreneurial activity. The research objective is to determine the determinants of product innovation in entrepreneurship. This study uses a qualitative method with a literature review technique which aims to provide information suggestions related to product innovation in entrepreneurship for SMEs. Analysis and search for articles involving themes with titles, abstracts, and keywords related to innovation, MSEs and products. Selection of articles according to writing needs, list of documents, type of article. The data collection technique in this study was a literature survey collected from the database using Harzing's Publish or Perish (PoP). This study outlines some of the previous research reference findings and explores the product innovation of MSEs. Found that the determinants of product innovation for micro and small businesses, competition between companies, quality of human resources and inclusive digitalization